Acquired hypothyroidism, iodine status and hearing impairment in adults: A pilot study - Tereza Grimmichova; Ludmila Verespejova; Zuzana Urbaniova; Martin Chovanec; Martin Hill; Radovan Bilek (PLoS ONE, 2025)
Objectives Hearing impairment can have major impacts on behavior, educational attainment, social status, and quality of life. In congenital hypothyroidism, the incidence of hearing impairment reaches 35–50%, while in acquired hypothyroidism there is a reported incidence of 25%. Despite this, knowledge of the pathogenesis, incidence and severity of hearing impairment remains greatly lacking. The aim of our study was to evaluate hearing in patients with acquired hypothyroidism. Methods 30 patients with untreated and newly diagnosed peripheral hypothyroidism (H) and a control group of 30 healthy probands (C) were enrolled in the study. Biochemical markers were measured, including median iodine urine concentrations (IUC) µg/L. The hearing examination included a subjective complaint assessment, otomicroscopy, tympanometry, transitory otoacoustic emission (TOAE), tone audiometry, and brainstem auditory evoked potential (BERA) examinations. The Mann-Whitney U test, Fisher’s Exact test and multivariate regression were used for statistical analysis. Results The H and C groups had significantly different thyroid hormone levels (medians with 95% CI) TSH mU/L 13.3 (8.1, 19.3) vs. 1.97 (1.21, 2.25) p =  0 and fT4 pmol/L 10.4 (9.51, 11.1) vs. 15 (13.8, 16.7) p =  0. The groups did not significantly differ in age 39 (34, 43) vs. 41 (36,44) p =  0.767 and IUC 142 (113, 159) vs. 123 (101, 157) p =  0.814. None of the hearing examinations showed differences between the H and C groups: otomicroscopy (p =  1), tympanometry (p =  1), TOAE (p =  1), audiometry (p =  0.179), and BERA (p =  0.505). Conclusions We did not observe any hearing impairment in adults with acquired hypothyroidism, and there were no associations found between hearing impairment and the severity of hypothyroidism or iodine status. However, some forms of hearing impairment, mostly mild, were very common in both studied groups.